Nutritional Quality of Tree and Understorey Forage in Silvopastoral Systems - Lowry, J Brian; Wilson, John R (Annals of Arid Zone, 2016)
In silvopastoral systems trees may provide feed directly, and also affect the composition and quality of sub-canopy vegetation. Green leaves may be available as feed from thinning of unwanted trees, from the pruning of trees to obtain good log form, from lopping of larger living trees, and from the canopy at final harvest. Perhaps of more significance is the annual seasonal fall of leaf, flower or pod, the amount and quality of each being a feature of individual tree species. As fallen tree leaf is rarely considered aÂ· feed resource, we review published records of its . use as feed in a variety of habitats and argue that there are good grounds for consicjering it to be particularly relevant as feed in the semi-arid tropics. Quality is obviously less' than for green leaf, with protein reduced by about 50%. However, higher fragmentability may make it a useful supplement to mature tropical grass . The effect of. trees on the quality of sub-canopy pasture is more complex than that of shade alone, which can affect quality in either direction. Water relations are highly dependent on tree species, usually reducing availability for the grass, but some trees utilize water from deeper soil to the benefit of the grass. The most marked effects on quality are when the sub-canopy environment fosters a higher quality species (often Panicum maximum var trichoglume) than that in the surrounding area. We review the published cases where positive effects on sub-canopy vegetation have been recorded.